Intelligent design process of grain boundary additive alloy for double main phase nd-cerium-iron-b rare earth permanent magnet material

CN122455535BActive Publication Date: 2026-10-16南宁桂电电子科技研究院有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610924137.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-16
Estimated Expiration
2046-06-25

AI Technical Summary

Technical Problem

[0005]1.成分设计盲目性强:现有技术多依赖研发人员的经验进行晶界添加合金的元素配比选择,缺乏对相图数据的系统应用,难以实现添加合金与双主相的精准晶格匹配,常出现有害杂质相析出、主相纯度降低等问题,导致磁性能提升有限

Benefits of technology

[0029] 1. Intelligent ingredient matching design solves the problem of blind ingredient design in traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122455535B_ABST
    Figure CN122455535B_ABST
Patent Text Reader

Abstract

The application discloses an intelligent design process of a grain boundary additive alloy of a double-main-phase Nd-Ce-Fe-B rare earth permanent magnet material, and belongs to the technical field of rare earth permanent magnet material preparation. The element proportion of the grain boundary additive alloy is accurately screened through an intelligent algorithm model, key process parameters such as annealing temperature and time are optimized, and the synergistic effect of multiple elements is realized. The application solves the problems of blindness in component design and experience dependence in parameters in the traditional process, the remanence of the prepared material is above 1.41T, the coercive force is above 15.2kOe, the maximum magnetic energy product is above 42.5MGOe, the temperature stability and corrosion resistance are significantly improved, and the cost is greatly reduced, so that the application is suitable for high-end fields such as new energy and electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rare earth permanent magnet material preparation technology, specifically to a smart design process for grain boundary alloying of dual-phase Nd-Ce-Fe-B rare earth permanent magnet materials. Background Technology

[0002] Rare earth permanent magnet materials, as key basic materials for modern industry, have been widely used in new energy vehicles, wind power generation, electronic information, medical devices, and other fields due to their excellent magnetic properties. Among them, Nd-Fe-B permanent magnet materials have become one of the most widely used rare earth permanent magnet materials due to their outstanding advantages such as high remanence, high coercivity, and high maximum energy product. As high-end equipment develops towards high efficiency, miniaturization, and lightweighting, higher requirements are placed on the comprehensive performance of Nd-Fe-B permanent magnet materials. This requires not only further improvement in magnetic properties but also enhancement of temperature stability and corrosion resistance, while simultaneously reducing production costs and alleviating the supply and demand imbalance of rare earth resources.

[0003] Dual-phase Nd-Ce-Fe-B permanent magnet materials are created by introducing two or more main phases (such as Nd2Fe). 14 B and Ce2Fe 14 (B) Utilizing the magnetic coupling between the main phases, Nd can be partially replaced by inexpensive rare earth elements such as Ce while maintaining high magnetic properties, effectively reducing raw material costs and becoming a research hotspot in recent years. However, the grain boundary structure of dual-main-phase Nd-Ce-Fe-B materials is complex, and the interfacial bonding state between the main phases and the grain size distribution significantly affect the magnetic properties. Grain boundary alloying is a key means to improve the performance of dual-main-phase Nd-Ce-Fe-B materials. It can enhance the magnetic properties and stability of the material by optimizing grain boundary composition, refining grains, strengthening grain boundary bonding, and suppressing eddy current losses.

[0004] Currently, there are still many technical bottlenecks in the design and process optimization of grain boundary alloying for dual-phase Nd-Ce-Fe-B permanent magnet materials:

[0005] 1. Strong reliance on blind design in composition: Existing technologies largely depend on the experience of researchers in selecting the element ratios for grain boundary alloys, lacking a systematic application of phase diagram data. This makes it difficult to achieve precise lattice matching between the added alloy and the two main phases, often resulting in problems such as the precipitation of harmful impurity phases and reduced purity of the main phase, leading to limited improvement in magnetic properties. For example, in some processes, the amount of Zr added is determined solely by experience. Excessive addition leads to the precipitation of large amounts of non-magnetic phases such as Fe2Zr, which occupy the space of the main phase and affect magnetic flux transfer; insufficient addition fails to fully utilize the grain refinement effect, and the grain boundary's effect on hindering the movement of magnetic domain walls is poor.

[0006] 2. Lack of theoretical guidance for process parameter optimization: The selection of process parameters such as annealing temperature, annealing time, and heating rate is mostly determined through repeated experiments, without establishing a correlation model between parameters and phase composition and properties. This makes it difficult to achieve the optimal combination of parameters. For example, if the annealing temperature is too low, element diffusion is insufficient, the interface between the alloy added at the grain boundary and the main phase is not tight, and the phase structure does not reach equilibrium; if the temperature is too high, it will cause abnormal grain growth, reduce the grain boundary area, decrease the resistance to magnetic domain wall movement, and reduce magnetic properties.

[0007] 3. Difficulty in controlling the synergistic effect of multiple elements: The mechanisms of action of elements such as Nd, Ce, Fe, and Zr in grain boundary alloys are complex, and existing processes make it difficult to precisely control the synergistic effect of each element. For example, although Ce can replace Nd to reduce costs, excessive substitution will lead to a decrease in the magnetic moment of the main phase and easily form harmful phases such as CeFe3; Zr can refine grains, but it needs to work synergistically with rare earth elements to ensure phase structure stability, and traditional processes cannot accurately balance the proportion of each element.

[0008] 4. Low resource utilization: Nd is a key element in Nd-Fe-B permanent magnet materials. It is scarce and expensive. The substitution schemes of cheap rare earth elements such as Ce in the existing process are unreasonable. Either the substitution ratio is too low, and the cost reduction effect is not obvious; or the substitution ratio is too high, which leads to significant decay of magnetic properties. It is impossible to balance cost and performance.

[0009] 5. Insufficient temperature stability and corrosion resistance: The dual-phase Nd-Ce-Fe-B material prepared by traditional processes has a loose grain boundary structure and poor phase composition stability. When the temperature changes, the magnetic domain structure is easily affected, and the magnetic properties are significantly weakened. At the same time, the grain boundaries are easy to become channels for the invasion of corrosive media, resulting in poor corrosion resistance and limiting its application in harsh environments.

[0010] 6. Poor consistency in batch production: Due to the lack of intelligent means for optimizing composition design and process parameters, human error has a significant impact on product performance. During batch production, there are significant differences in phase structure, grain size, magnetic properties, etc. of materials from different batches, making it difficult to meet the strict requirements of high-end equipment for material consistency.

[0011] Therefore, developing a grain boundary addition alloy design process based on phase diagram data and intelligent algorithms to achieve precise optimization of composition and process parameters, enhance the synergistic effect of multiple elements, improve the comprehensive performance of dual-main-phase Nd-Ce-Fe-B permanent magnet materials, and reduce costs has become an urgent technical problem to be solved in the field of rare earth permanent magnet materials. Summary of the Invention

[0012] The purpose of this invention is to overcome the shortcomings of the prior art and provide an intelligent design process for grain boundary alloying of dual-phase Nd-Ce-Fe-B rare earth permanent magnet materials. Through intelligent means, the composition of the grain boundary alloying is precisely matched with the process parameters, which enhances the synergistic effect of multiple elements and significantly improves the magnetic properties, temperature stability, corrosion resistance and mechanical properties of the material. At the same time, it reduces production costs, improves the consistency of mass production and meets the application needs of high-end fields.

[0013] To achieve the above objectives, the present invention adopts the following technical solution:

[0014] A smart design process for grain boundary alloying in dual-phase Nd-Ce-Fe-B rare-earth permanent magnet materials includes the following steps:

[0015] (1) Constructing a phase diagram database of multi-component systems: Based on the main phase structure of dual-main-phase Nd-Ce-Fe-B permanent magnet materials, a phase diagram database of Nd-Fe-Zr and Ce-Fe-Zr systems was constructed, and rare earth elements Nd and Ce were selected. Alloy systems of transition metals Fe and Zr were prepared using a balanced process to adjust the composition, and phase characterization analysis was conducted to obtain experimental data of equilibrium phases under different element ratios. The composition ranges of each element were defined, including Nd, Ce, Fe, and Zr, with the total ratio normalized to 100 at.%, of which Nd content was 3.6-43.1 at.%, Ce content was 0-30.94 at.%, Zr content was 1.6-18.9 at.%, and Fe content was 35.5-94.8 at.%. The phase types, elemental compositions of each phase, phase region distribution boundaries, and component thresholds for easily precipitating harmful phases were recorded and stored for different compositions. At the same time, beneficial phases and harmful impurity phases in the system were distinguished and marked to form a phase diagram database with phase screening and constraint functions.

[0016] (2) Intelligent composition design based on intelligent algorithm model: According to the preset lower limit of permanent magnetic performance index as a constraint, the phase region matching algorithm is first called to traverse all the composition ratios in the phase diagram database, eliminate the ratios with harmful impurity phases, and screen to obtain a set of candidate compositions containing only beneficial phases; then, the machine learning performance prediction model is used to establish the correlation between element composition and permanent magnetic performance based on historical experimental data, and the candidate composition set is iteratively optimized to finally output the optimal alloy composition ratio that simultaneously meets the preset permanent magnetic performance requirements and has no harmful impurity phases.

[0017] (3) Intelligent optimization of process parameters: Based on single-factor experiments and multi-factor coupling analysis, intelligent optimization of process parameters: annealing temperature 850-950℃, annealing time 35-50 days, heating rate 8-12K / min, grain boundary addition mass fraction 4%-6%, and cooling method is furnace cooling or segmented cooling.

[0018] (4) Material preparation: The dual-phase Nd-Ce-Fe-B powder and the intelligently designed grain boundary alloy powder were mixed evenly in proportion, sintered under argon protection, and then annealed according to the optimized process parameters to obtain the dual-phase Nd-Ce-Fe-B rare earth permanent magnet material.

[0019] Furthermore, the data in step (1) includes the identification phase and EPMA component analysis results under different element ratios.

[0020] Furthermore, the intelligent algorithm model described in step (2) includes a phase region matching algorithm and a performance prediction model. The phase region matching algorithm is used to screen the element ratio of the phase without harmful impurities. The performance prediction model is based on a machine learning algorithm, with phase composition and element content as input and magnetic properties as output, to achieve precise optimization of the ratio.

[0021] Furthermore, the recognition phase of the grain boundary alloying in step (2) includes Nd. x Fe 23 Zr 6-x Fe 17 Nd 2-x Zr x Ce2Fe 17 CeFe2, Fe 23 At least two of Zr6 and Fe2Zr are present, and the harmful impurity phase is Fe. x Nd 1-x The content is less than 5 at.%.

[0022] Furthermore, the specific method of segmented cooling in step (3) is as follows: first, cool with the furnace to 600°C, and then air cool to room temperature at a rate of 5K / min.

[0023] Furthermore, the mixing mass ratio of the dual-phase Nd-Ce-Fe-B powder and the grain boundary added alloy powder in step (4) is 93:7-96:4.

[0024] Furthermore, the mixing method employs a planetary ball mill with a milling speed of 200-300 r / min and a milling time of 2-4 h.

[0025] Furthermore, in step (4), the sintering temperature under argon protection is 1050-1150℃, and the sintering time is 2-4h.

[0026] Furthermore, the sintering atmosphere is high-purity argon gas with a purity of ≥99.99%.

[0027] Furthermore, the main phase of the dual-main-phase Nd-Ce-Fe-B permanent magnet material is Nd2Fe. 14 B and Ce2Fe 14B, the mass ratio of the two is 1:1-3:1.

[0028] Compared with the prior art, the present invention has the following significant technical advantages:

[0029] 1. Intelligent ingredient matching design solves the problem of blind ingredient design in traditional methods.

[0030] This invention, based on a phase diagram database of the Nd-Fe-Zr and Ce-Fe-Zr systems, utilizes an intelligent algorithm model comprised of a phase region matching algorithm and a performance prediction model to achieve precise design of the alloy composition for grain boundary additions. Traditional processes rely on experience to select compositions, failing to fully consider phase region distribution patterns, which can easily lead to poor compatibility between the composition and the main phase lattice, resulting in the introduction of harmful impurity phases. The intelligent design process of this invention, however, can use the phase region matching algorithm to select element ratios free of harmful impurity phases and with high purity in the main phase, ensuring precise matching of the lattice constants of the grain boundary alloy with the dual main phases Nd-Ce-Fe-B, reducing grain boundary stress and promoting magnetic domain rotation. Simultaneously, the performance prediction model, based on machine learning algorithms, fully explores the composition-performance correlation patterns in historical experimental data, further optimizing the ratios and achieving precise control of magnetic properties. This intelligent composition design method fundamentally solves the blindness of traditional process composition design, ensuring synergistic compatibility between the added alloy and the main phase, laying the foundation for improved material performance.

[0031] 2. Intelligent optimization of process parameters enables precise control of phase structure and properties.

[0032] In existing technologies, the selection of process parameters is often achieved through repeated experiments, without establishing a scientific correlation between parameters and phase composition and properties. This leads to difficulties in achieving optimal parameter combinations, often resulting in incomplete phase transformation and uneven grain size. This invention systematically studies the influence of key process parameters such as annealing temperature, annealing time, and heating rate on the phase structure and properties of materials through single-factor experiments and multi-factor coupled analysis, clarifying the mechanism of action and optimal range of each parameter. An intelligent algorithm model integrates single-factor and orthogonal experimental data to establish a correlation model between process parameters, phase composition, and properties. This model can automatically optimize parameter combinations based on target performance, ensuring a synergistic match between process parameters and composition design. For example, when adding alloy components to specific grain boundaries, the model can precisely select the annealing temperature and time to ensure sufficient element diffusion, promote the formation of stable phases, and avoid problems such as grain coarsening or incomplete phase transformation. This intelligent optimization method of process parameters achieves precise control of phase structure and properties, significantly improving the stability and reliability of material properties.

[0033] 3. Enhanced by the synergistic effect of multiple elements, balancing magnetic properties and overall performance.

[0034] In dual-phase Nd-Ce-Fe-B materials, the interaction mechanisms of elements such as Nd, Ce, Fe, and Zr are complex, and traditional processes struggle to precisely control the synergistic effects of each element, often resulting in compromises. This invention, through intelligent process design, precisely balances the proportions of each element, maximizing the synergistic effect of multiple elements. Nd serves as the main phase, Nd₂Fe. 14 B is the core element, ensuring the material's basic magnetic properties; Ce has an atomic radius close to that of Nd, allowing it to partially replace Nd in the main phase, reducing costs while forming Ce₂Fe with Fe. 17 Beneficial phases such as CeFe2 optimize grain boundary composition and enhance grain boundary bonding; Zr can refine grains and form Fe 23 Stable intermetallic compounds such as Zr6 and Fe2Zr improve grain boundary structure, inhibit grain growth, and enhance temperature stability. Fe, as the metallic matrix, intertwines with rare earth elements and Zr to form intermetallic compounds, enhancing the material's mechanical properties. Under intelligently designed composition and process parameters, the elements work synergistically to ensure high magnetic properties while significantly improving temperature stability, corrosion resistance, and mechanical properties, solving the technical challenge of achieving multiple performance indicators simultaneously using traditional processes.

[0035] 4. Efficient resource utilization significantly reduces production costs.

[0036] As a key element in rare-earth permanent magnet materials, Nd is scarce and expensive, and its usage directly affects material costs. Existing technologies use inexpensive rare-earth elements like Ce as substitutes, but these are either too low, resulting in minimal cost reduction, or too high, leading to significant degradation of magnetic properties. This invention, through intelligent process design, precisely determines the optimal Ce substitution ratio for Nd, maximizing Ce substitution without significantly reducing magnetic properties. Since Ce's market price is far lower than Nd's, reasonable substitution can significantly reduce material costs. Simultaneously, intelligent component design avoids element waste, ensuring each element functions optimally and improving rare-earth resource utilization. Furthermore, intelligent optimization of process parameters shortens annealing time, reduces production energy consumption, further lowers production costs, and achieves a synergistic improvement in economic benefits and performance.

[0037] 5. Improved consistency in mass production to meet the needs of high-end applications.

[0038] Traditional processes, lacking intelligent means for composition design and parameter optimization, are highly susceptible to human error that significantly impacts product performance. During mass production, significant variations exist between batches of materials in phase structure, grain size, and magnetic properties, making it difficult to meet the stringent consistency requirements of high-end equipment. This invention's intelligent design process achieves precise control of composition and process parameters through algorithmic models, reducing human interference. In mass production, only the target performance parameters need to be input to automatically generate a unified composition scheme and process parameters, ensuring a high degree of consistency in the preparation process of each batch of materials. Simultaneously, the intelligent process effectively controls the uniformity of grain size and phase composition, reducing performance fluctuations between batches.

[0039] 6. Overall performance has been comprehensively optimized, expanding application scenarios.

[0040] Existing technologies for preparing dual-phase Nd-Ce-Fe-B materials often suffer from imbalances in overall performance, including magnetic properties, temperature stability, and corrosion resistance, limiting their applications. This invention achieves comprehensive optimization of the material's overall performance through intelligent process design. Regarding magnetic properties, the material exhibits a Br content exceeding 1.41T and a H content exceeding 1.41T. cj Above 15.2 kOe, (BH) max It is above 42.5 MGOe; in terms of temperature stability, the remanence temperature coefficient α(B) is above 42.5 MGOe. r The coercivity temperature coefficient β(H) is above -0.032% / ℃. cj The magnetic properties exhibit a low corrosion rate (-0.45% / ℃) and slow decay within a temperature range of -40℃ to 150℃. Regarding corrosion resistance, the salt spray corrosion rate is below 0.0025 mm / a, enabling stable operation in harsh environments such as humid and salt-spray conditions. In terms of mechanical properties, the compressive strength exceeds 1248 MPa, enhancing the material's resistance to damage during assembly and use. This comprehensive optimization of overall performance makes the material suitable for various high-end applications, including new energy vehicle drive motors, wind turbines, permanent magnet components for electronic devices, and permanent magnet parts for medical devices, thus expanding the application scope of dual-phase Nd-Ce-Fe-B permanent magnet materials. Attached Figure Description

[0041] Figure 1 A flowchart of the intelligent design process for adding alloys to the grain boundaries of the dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet material of the present invention;

[0042] Figure 2 This is a flowchart illustrating the operation of the intelligent algorithm model.

[0043] Figure 3 The image shows the EPMA-BSE image of the dual-phase Nd-Ce-Fe-B rare earth permanent magnet material prepared in Example 1.

[0044] Figure 4 The XRD pattern of the dual-phase Nd-Ce-Fe-B rare earth permanent magnet material prepared in Example 2;

[0045] Figure 5 The image shows the EPMA-BSE image of the dual-phase Nd-Ce-Fe-B rare earth permanent magnet material prepared in Example 2.

[0046] Figure 6 The XRD pattern of the dual-main-phase Nd-Ce-Fe-B rare earth permanent magnet material prepared in Example 3;

[0047] Figure 7 The image shows the EPMA-BSE image of the dual-phase Nd-Ce-Fe-B rare earth permanent magnet material prepared in Example 3.

[0048] Figure 8 This graph shows the effect of different annealing temperatures on the magnetic properties of the material. In the graph, the horizontal axis (1-5) corresponds to the gradient annealing samples at 800℃, 850℃, 900℃, 950℃, and 1000℃, respectively. The right vertical axis represents the annealing temperature (℃) represented by the blue bars, and the left vertical axis represents the magnetic property index. The yellow line represents the coercivity H. cj (kOe), maximum energy product of the green line (BH) max (MGOe);

[0049] Figure 9 This graph shows the effect of different annealing times on the magnetic properties of the material. In the graph, the horizontal axis (1-5) corresponds to the samples annealed at 30d, 35d, 45d, 50d, and 60d, respectively; the right vertical axis is represented by blue bars, which represent annealing time (in days); the left vertical axis represents the magnetic property index, and the yellow line represents the coercivity H. cj (kOe), the green line represents the maximum magnetic energy product (BH). max (MGOe);

[0050] Figure 10 The graph shows the effect of different grain boundary mass fractions on the magnetic properties of the material. In the graph, the horizontal axis (1-5) corresponds to grain boundary mass fractions of 3%, 4%, 5%, 6%, and 7%, respectively; the right vertical axis corresponds to the blue bars, representing the amount of grain boundary added (mass fraction %); the left vertical axis represents the magnetic property index, and the yellow line represents the coercivity H. cj (kOe), the green line represents the maximum magnetic energy product (BH). max (MGOe);

[0051] Figure 11 The graph shows the effect of different heating rates on the magnetic properties of the material. In the graph, the horizontal axis (1-5) corresponds to heating rates of 6, 8, 10, 12, and 14 K / min, respectively; the right vertical axis is represented by blue bars, which represent the heating rate (in K / min); the left vertical axis represents the magnetic property index, and the yellow line represents the coercivity H. cj (kOe), the green line represents the maximum magnetic energy product (BH).max (MGOe);

[0052] Figure 12 The graph shows the magnetic properties of the material with different Ce substitution ratios for Nd. In the graph, the horizontal axis (1-5) corresponds to Ce substitution ratios of 0, 3, 5, 10, and 15 at.% respectively; the right vertical axis corresponds to the blue bars, representing the Ce substitution ratio for Nd (in at.%); the left vertical axis represents the magnetic property index, and the yellow line represents the coercivity H. cj (kOe), the green line represents the maximum magnetic energy product (BH). max (MGOe). Detailed Implementation

[0053] The intelligent design process of the rare earth Nd-Ce-Fe-B permanent magnet material of the present invention will be described in detail below with reference to the accompanying drawings and experimental data.

[0054] In embodiments of the present invention, such as Figure 1 As shown, a smart design process for grain boundary alloying of dual-phase Nd-Ce-Fe-B rare earth permanent magnet materials includes phase diagram database construction, intelligent composition design, intelligent optimization of process parameters, and material preparation, specifically including the following steps:

[0055] Step 1: Phase Diagram Database Construction

[0056] 1.1 Sources of Basic Experimental Data

[0057] (1) Experimental data of the Nd-Fe-Zr ternary system using a 900℃ isothermal cross section:

[0058] Experimental temperature: 900℃ (1173K);

[0059] Testing methods: High-temperature equilibrium annealing + quenching + EPMA electron probe microanalysis and metallographic phase identification;

[0060] Variables: Gradient control of the atomic percentage ratio of Nd, Fe, and Zr, and characterization of each equilibrium phase after long-term heat preservation to reach thermodynamic equilibrium.

[0061] (2) Experimental conditions for Ce-Fe-Zr ternary system: isothermal annealing at 1173K for 45 days to fully achieve phase equilibrium;

[0062] After annealing, the samples were water-cooled and quenched to lock in the high-temperature equilibrium structure. Metallographic observation, XRD phase identification, and EPMA quantitative composition analysis were carried out in sequence to obtain phase evolution data for the entire composition range.

[0063] 1.2 Database includes elements and composition ranges (atomic percentage at.%)

[0064] The quaternary element system consists of Nd, Ce, Fe, and Zr, with a total normalized ratio of 100 at.%, of which Nd content is 3.6-43.1 at.%, Ce content is 0-30.94 at.%, Zr content is 1.6-18.9 at.%, and Fe content is 35.5-94.8 at.%.

[0065] 1.3 Core Database Storage Content

[0066] (1) Phase identification results at each ratio: distinguishing between beneficial phase and harmful impurity phase;

[0067] (2) Quantitative EPMA analysis: Precise composition of Nd / Ce / Fe / Zr elements in each equilibrium phase;

[0068] (3) Distribution law of phase regions in ternary isothermal section: boundary of single / double / three-phase coexistence region, critical composition point of phase transformation;

[0069] (4) Safety component threshold: Define the component window without harmful impurity phases to avoid the ratio range where harmful phases are easily precipitated in advance.

[0070] 1.4 Delineation of Harmful / Beneficial Phases

[0071] (1) Harmful impurity phase: Soft magnetic impurities significantly deteriorate coercivity and squareness of the demagnetization curve;

[0072] (2) Beneficial aspects of the objective: , , , , , ;

[0073] The database will mark whether harmful phases are generated under any ratio, as a hard constraint for subsequent screening.

[0074] Step 2: Intelligent Ingredient Design

[0075] Intelligent component design is performed using an intelligent algorithm model. The intelligent algorithm model consists of a coupled phase region matching algorithm and a machine learning performance prediction model. The operation flowchart of the intelligent algorithm model is shown below. Figure 2 This includes the following steps:

[0076] Process Startup: The program begins by inputting the minimum performance indexes required for the material.

[0077] Initial screening scope construction: All alloy proportions to be screened are generated using a phase region matching algorithm, and each proportion is verified sequentially.

[0078] Retrieve the phase information corresponding to this ratio to determine whether harmful impurities are generated;

[0079] If harmful impurities are present, the mixture ratio is directly removed, and the process returns to the traversal stage to verify the next mixture ratio.

[0080] If there are no harmful impurities, this ratio will be included in the candidate component pool.

[0081] Iterative performance optimization: Input the proportions from the candidate component pool into the machine learning model to perform performance prediction and iterative optimization; verify whether the current proportions all meet the lower limits of the three magnetic properties.

[0082] If the target is not met, return to the model and continue iterating to find the best solution.

[0083] If all standards are met, the solution is deemed acceptable.

[0084] Process completion: Output the optimal alloy ratio that satisfies the requirements for phase purity and magnetic properties, and the process ends.

[0085] The key details are as follows:

[0086] 2.1 Input Constraints: Hard Specifications of Target Magnetic Properties

[0087] User inputs the lower limit threshold for permanent magnetic properties:

[0088] (1) Remanence

[0089] (2) Innate coping force

[0090] (3) Maximum magnetic energy product

[0091] 2.2 First Module: Phase Region Matching Algorithm (Pre-screening, eliminating unqualified ratios)

[0092] (1) Traverse all Nd-Ce-Fe-Zr ratio schemes in the database;

[0093] (2) Retrieve the equilibrium phase information corresponding to this ratio;

[0094] (3) Constraint determination:

[0095] If the system has a large number of Harmful impurities → Directly remove from this formulation;

[0096] Only the candidate mix proportions where all phases are pre-defined beneficial phases are retained;

[0097] (4) Output: A pool of candidate components without harmful impurities, narrowing the optimization range.

[0098] 2.3 Module 2: Machine Learning Performance Prediction Model (Matching Optimization)

[0099] (1) Model training basics:

[0100] Training set: Massive historical experimental data on Nd-Ce-Fe-Zr grain boundary alloys (elemental content + measured values) );

[0101] Algorithm type: Machine learning regression model (gradient boosting / random forest / neural network are all compatible);

[0102] (2) Mapping relationship construction: learning the nonlinear mapping from the atomic fractions of Nd, Ce, Fe, and Zr to the three magnetic properties;

[0103] (3) Iterative optimization:

[0104] Performance prediction is performed on the candidate matching ratios after phase region matching and screening, and the optimal ratio is found through a traversal process.

[0105] (4) Output the optimal solution: the only / optimal element ratio that simultaneously satisfies the lower limit of three magnetic properties and all beneficial phases.

[0106] Step 3: Intelligent optimization of process parameters

[0107] The optimal range of key process parameters was determined through single-factor experiments and multi-factor coupling analysis. Single-factor experiments investigated the effects of Nd content, Zr content, annealing temperature, annealing time, grain boundary addition mass fraction, heating rate, and Ce substitution ratio on material properties, clarifying the optimal values ​​for each parameter. Multi-factor coupling analysis, through orthogonal experiments, studied the interaction between parameters, ultimately determining the optimal combination of process parameters: annealing temperature 850-950℃, annealing time 35-50 days, heating rate 8-12 K / min, grain boundary addition mass fraction 4%-6%, and cooling method either furnace cooling or segmented cooling (furnace cooling to 600℃ followed by air cooling to room temperature at a rate of 5 K / min).

[0108] Step 4: Material Preparation

[0109] The dual-main-phase Nd-Ce-Fe-B powder (Nd2Fe) 14 B and Ce2Fe 14 The Nd-Ce-Fe-B rare earth permanent magnet material is prepared by mixing B (mass ratio 1:1-3:1) with intelligently designed grain boundary alloy powder at a mass ratio of 93:7-96:4 and ball milling at 200-300 r / min for 2-4 hours using a planetary ball mill to ensure uniform mixing. The mixed powder is then placed in a vacuum sintering furnace and sintered at 1050-1150℃ for 2-4 hours under the protection of high-purity argon (purity ≥99.99%). Subsequently, it is annealed according to optimized process parameters and cooled to room temperature to obtain a dual-phase Nd-Ce-Fe-B rare earth permanent magnet material.

[0110] Technical principle of the invention:

[0111] The intelligent design process of this invention is based on phase diagram thermodynamics, magnetic domain dynamics, and machine learning algorithms. Through precise control of composition and process parameters, it improves the overall performance of dual-main-phase Nd-Ce-Fe-B permanent magnet materials. Its core technical principle is as follows:

[0112] 1. Mechanism of action of raw materials

[0113] (1) Nd element: Nd is the main phase of the dual-phase Nd-Ce-Fe-B permanent magnet material, namely Nd2Fe. 14 The core component of boron, Nd atoms, forms a crystal structure with a high magnetic moment through strong exchange coupling with Fe atoms, which is the basis for the material's excellent magnetic properties. In grain boundary alloys, an appropriate amount of Nd can promote Nd... x Fe 23 Zr 6-x Fe 17 Nd 2-x Zr x The formation of beneficial phases, such as Nd2Fe, allows these phases to interact with the main phase Nd2Fe. 14 B forms a good lattice match, reduces magnetic resistance at grain boundaries, and increases the resistance to the movement of magnetic domain walls, thereby improving the coercivity and maximum magnetic energy product of the material.

[0114] (2) Ce element: As an inexpensive rare earth element, Ce has an atomic radius similar to that of Nd (Nd atomic radius 181 pm, Ce atomic radius 183 pm), and has the ability to partially substitute Nd into the main phase Nd2Fe. 14 Conditions for B-type lattices. Ce can be formed by replacing Nd with Ce. 14 Although the magnetic moment of Ce is slightly lower than that of Nd in the B main phase, the cost of raw materials can be significantly reduced by intelligently controlling the substitution ratio (5-10 at.%) without significantly decreasing the magnetic properties. Furthermore, Ce and Fe can also form Ce₂Fe. 17 Grain boundary phases such as CeFe2 have good chemical stability and mechanical properties. They can optimize the grain boundary structure, enhance the grain boundary bonding force, and form a dense oxide film, thereby improving the corrosion resistance of the material.

[0115] (3) Fe element: Fe is the main component of the metallic matrix of the material. It not only provides a coordination environment for rare earth elements such as Nd and Ce, but also forms intermetallic compounds with high magnetic properties (such as Nd2Fe). 14 B, Ce2Fe 14 B), can also form Fe with Zr 23 Intermetallic compounds such as Zr6 and Fe2Zr. The good electrical and thermal conductivity of Fe facilitates heat dissipation during the operation of the material, reducing the impact of temperature rise on magnetic properties; at the same time, Fe, as a matrix, can enhance the mechanical strength of the material, ensuring that the material is not easily damaged during assembly and use.

[0116] (4) Zr: Zr is a key element for improving the microstructure and temperature stability of materials. Zr has a relatively large atomic radius (160 pm), which hinders grain growth and refines the grains. After grain refinement, the grain boundary area increases, increasing the resistance to the movement of magnetic domain walls, thereby improving the coercivity of the material. Furthermore, Zr forms Fe with Fe... 23 Intermetallic compounds such as Zr6 and Fe2Zr possess high melting points and good thermal stability, which can improve the phase structure stability of materials and reduce the impact of temperature changes on magnetic domain structure, thereby enhancing the temperature stability of materials. Simultaneously, these intermetallic compounds can also enhance the chemical stability of grain boundaries, reduce the erosion of grain boundaries by corrosive media, and improve the corrosion resistance of materials.

[0117] 2. Mechanism of synergistic effect of raw materials

[0118] The intelligent design process of this invention achieves the synergistic effect of each element by precisely controlling the ratio of Nd, Ce, Fe, and Zr, specifically manifested as follows:

[0119] (1) Synergistic substitution of Nd and Ce: Nd ensures the high magnetic moment of the main phase, while Ce partially replaces Nd to reduce costs. The synergistic effect of the two makes the magnetic properties and costs of the main phase reach the best balance. By controlling the substitution ratio of Ce through intelligent design, the decrease in the magnetic moment of the main phase and the precipitation of harmful phases caused by excessive substitution are avoided, ensuring the continuity of the main phase and the magnetic coupling effect.

[0120] (2) Synergistic optimization of Zr and rare earth elements (Nd, Ce): Zr refines grains, providing more resistance to the movement of magnetic domain walls; rare earth elements optimize grain boundary composition and enhance grain boundary bonding. The synergistic effect of the two improves the grain boundary structure, reduces the magnetic resistance at the grain boundaries, and at the same time improves the stability of the phase structure, thus achieving a synergistic improvement in magnetic properties and temperature stability.

[0121] (3) Synergistic phase formation of Fe with other elements: Fe, as the matrix, forms a high magnetic performance main phase with Nd and Ce, and a stable intermetallic compound with Zr. The three work together to construct a stable structure of "main phase-grain boundary phase", which not only ensures the high magnetic performance of the material, but also enhances its mechanical properties and corrosion resistance.

[0122] 3. The necessity and importance of selecting process parameters

[0123] (1) Annealing temperature: The annealing temperature of 850-950℃ is selected based on the thermodynamic laws of the phase diagram and the kinetics of element diffusion. This temperature range can provide sufficient thermodynamic conditions for element diffusion, promote element exchange between the alloy added at the grain boundary and the main phase, realize the complete phase transformation, and form a stable main phase and grain boundary phase. When the temperature is too low (below 850℃), the element diffusion rate is slow, the phase transformation is incomplete, a large number of metastable phases exist, the compositional uniformity at the grain boundary is poor, resulting in poor magnetic properties and stability; when the temperature is too high (above 950℃), the grains will grow abnormally, the grain boundary area will decrease, the resistance to magnetic domain wall movement will decrease, and new harmful phases (such as coarsened Fe phase) may appear, which will destroy the continuity of the main phase and lead to a decrease in magnetic properties.

[0124] (2) Annealing time: An annealing time of about 45 days is the key to ensuring complete phase transformation and homogenization of composition. If the annealing time is too short (less than 35 days), the element diffusion is insufficient, the enrichment or depletion of composition at the grain boundaries cannot be eliminated, the phase structure does not reach equilibrium, and the material properties are unstable. If the annealing time is too long (more than 50 days), although the phase structure is basically in equilibrium, it will increase production energy consumption and cost, and may lead to a small amount of grain growth, which will have a slight negative impact on magnetic properties and no significant performance improvement. Therefore, 45 days is the optimal annealing time.

[0125] (3) Heating rate: A heating rate of about 10 K / min can avoid excessive temperature gradient and thermal stress inside the material. If the heating rate is too fast (above 12 K / min), the temperature difference between the inside and outside of the material will be large, and the thermal stress will cause grain boundary cracking, uneven grain distribution, and even thermal defects, which will destroy the integrity of the magnetic domain structure. If the heating rate is too slow (below 8 K / min), the production efficiency will be low, and the long-term low temperature stage may cause elements to precipitate prematurely, forming an uneven phase structure and affecting the uniformity of magnetic properties.

[0126] (4) Grain boundary addition mass fraction: A grain boundary addition mass fraction of about 5% is the key to achieving grain boundary optimization and magnetic performance balance. If the addition amount is too small (below 4%), the added alloy at the grain boundary is insufficient to completely cover the surface of the main phase grains, and cannot fully improve the grain boundary structure and composition, thus having limited effect on refining grains and stabilizing phase structure; if the addition amount is too large (above 6%), the excessive added alloy will form a thick grain boundary phase at the grain boundary, hindering the transmission of magnetic flux, leading to a decrease in remanence, and at the same time, the added alloy may agglomerate, destroying the continuity of the main phase and affecting magnetic performance.

[0127] (5) Cooling method: Furnace cooling or segmented cooling can reduce the impact of temperature changes on phase structure. Rapid cooling will cause the phase structure to freeze, forming a metastable phase, which will affect the stability of the material; furnace cooling or segmented cooling can make the material cool down slowly, ensuring that the phase structure is formed in a thermodynamic equilibrium state, reducing internal stress and improving the performance stability of the material.

[0128] 4. Unexpected technical effects

[0129] Through the intelligent design process of this invention, the following unexpected technical effects have been achieved:

[0130] (1) Significant improvement in magnetic properties: Compared with traditional processes, the Br and H of the material are significantly improved. cj (BH) max Significant improvements were achieved in both aspects, with a substantial increase in the uniformity and stability of magnetic properties. This is due to the intelligent design that enabled precise matching of composition and process parameters, optimized the structure of the main phase and grain boundary phase, and reduced the obstruction to the movement of magnetic domain walls.

[0131] (2) Significant improvement in temperature stability: The absolute values ​​of the remanence temperature coefficient and coercivity temperature coefficient are significantly reduced. The magnetic properties of the material decay slowly in a wide temperature range of -40℃ to 150℃. This is because the formation of Fe-Zr intermetallic compounds improves the thermal stability of the phase structure, and the optimization of grain boundaries reduces the influence of temperature changes on the magnetic domain structure.

[0132] (3) Breakthrough improvement in corrosion resistance: The salt spray corrosion rate was reduced by 45.8%. This is because the addition of Ce formed a dense oxide film, and the Zr element improved the chemical stability of the grain boundaries and reduced the intrusion of corrosive media.

[0133] (4) Synergistic optimization of mechanical and magnetic properties: The compressive strength was increased by 16.3%, while the magnetic properties were not affected. This is because the refined grains and uniform phase distribution enhanced the mechanical load-bearing capacity of the material, and the improved grain boundary bonding force prevented grain boundary cracking under stress.

[0134] (5) Balance between cost and performance: Under the premise that the magnetic properties remain basically unchanged, the material cost is reduced by 8%-22%, achieving a synergistic improvement in economic benefits and performance.

[0135] To make the present invention more fully disclosed, more specific embodiments are described below.

[0136] Example 1

[0137] A smart design process for grain boundary alloying in dual-phase Nd-Ce-Fe-B rare-earth permanent magnet materials includes the following steps:

[0138] (1) Composition design: Based on the phase diagram database, the alloy composition for grain boundary addition was screened through an intelligent algorithm model, and the Nd content was determined to be 3.6 at.%, Fe content 94.8 at.%, and Zr content 1.6 at.%, with Nd being the identified phase. x Fe 23 Zr 6-x Fe17 Nd 2-x Zr x It contains a small amount of Fe phase and no harmful impurity phases.

[0139] (2) Process parameter optimization: The process parameters were optimized by intelligent model. The annealing temperature was 900℃, the annealing time was 45 days, the heating rate was 10K / min, the cooling method was furnace cooling, and the grain boundary added 5% by mass.

[0140] (3) Material preparation: The dual-phase Nd-Ce-Fe-B powder (Nd2Fe) was prepared. 14 B and Ce2Fe 14 B (at a mass ratio of 2:1) and grain boundary alloying powder were mixed at a mass ratio of 95:5 and ball-milled for 3 hours at 250 r / min using a planetary ball mill. The mixed powder was then placed in a vacuum sintering furnace and sintered at 1100℃ for 3 hours under high-purity argon protection. Subsequently, annealing was performed according to optimized process parameters, and after cooling to room temperature, a dual-phase Nd-Ce-Fe-B rare earth permanent magnet material was obtained. The sample was tested and obtained... Figure 3 EPMA-BSE image, by Figure 3 It can be seen that the sample matrix has clear grain outlines and reasonable grain size distribution; uniform and continuous functional second phases precipitate at the grain boundaries, without large-area accumulation of harmful impurities, and the cleanliness is good.

[0141] Example 2

[0142] A smart design process for grain boundary alloying in dual-phase Nd-Ce-Fe-B rare-earth permanent magnet materials includes the following steps:

[0143] (1) Composition design: Based on the phase diagram database, the grain boundary alloy composition was screened by an intelligent algorithm model, and the Ce content was determined to be 7.75 at.%, Fe content to be 90.94 at.%, and Zr content to be 1.31 at.%, with Ce2Fe as the identified phase. 17 and Fe 23 Zr6 phase, without harmful impurity phases.

[0144] (2) Process parameter optimization: The process parameters were optimized by intelligent model. The annealing temperature was 1173K (900℃), the annealing time was 45 days, the heating rate was 10K / min, the cooling method was furnace cooling, and the grain boundary added mass fraction was 6%.

[0145] (3) Material preparation: The dual-phase Nd-Ce-Fe-B powder (Nd2Fe) was prepared. 14 B and Ce2Fe 14B (at a mass ratio of 1:1) and grain boundary alloying powder were mixed at a mass ratio of 94:6 and ball-milled at 220 r / min for 3.5 h using a planetary ball mill. The mixed powder was then placed in a vacuum sintering furnace and sintered at 1080 °C for 3.5 h under high-purity argon protection. Subsequently, it was annealed according to optimized process parameters and cooled to room temperature to obtain a dual-phase Nd-Ce-Fe-B rare earth permanent magnet material. The sample was tested and obtained... Figure 4 XRD patterns and Figure 5 EPMA-BSE image, by Figure 4 It can be seen that the main peak of the sample's XRD pattern corresponds to the main magnetic phase Ce2Fe. 17 The standard diffraction peaks are highly matched, with sharp peak shapes and stable baselines, indicating excellent crystallinity; only a small amount of Fe is generated. 23 Zr6 auxiliary phase, with no harmful impurity diffraction peaks precipitated. Figure 5 It can be seen that the light and dark phases of the sample are evenly and alternately distributed, the interface between the two phases is flat and clear, and there are no coarse harmful impurities or continuous impurities precipitated. The grain size is moderate, the structure is dense and clean, and the uniform two-phase structure can enhance the magnetic exchange coupling effect, which is beneficial to improving the overall magnetic properties of the material.

[0146] Example 3

[0147] A smart design process for grain boundary alloying in dual-phase Nd-Ce-Fe-B rare-earth permanent magnet materials includes the following steps:

[0148] (1) Composition design: Based on the phase diagram database, the alloy composition for grain boundary addition was screened through an intelligent algorithm model, and the Ce content was determined to be 30.94 at.%, the Fe content to be 66.59 at.%, and the Zr content to be 2.47 at.%, with CeFe2 and Fe phases identified as the two phases. 23 Zr6 phase, without harmful impurity phases.

[0149] (2) Process parameter optimization: The process parameters were optimized by intelligent model. The annealing temperature was 1173K (900℃), the annealing time was 45 days, the heating rate was 12K / min, the cooling method was furnace cooling, and the grain boundary added mass fraction was 7%.

[0150] (3) Material preparation: The dual-phase Nd-Ce-Fe-B powder (Nd2Fe) was prepared. 14 B and Ce2Fe 14 B (at a mass ratio of 1:1) and grain boundary alloying powder were mixed at a mass ratio of 93:7 and ball-milled for 2 hours at 300 r / min using a planetary ball mill. The mixed powder was then placed in a vacuum sintering furnace and sintered at 1050℃ for 4 hours under high-purity argon protection. Subsequently, annealing was performed according to optimized process parameters, and after cooling to room temperature, a dual-phase Nd-Ce-Fe-B rare earth permanent magnet material was obtained. The sample was then tested to obtain… Figure 6XRD patterns and Figure 7 EPMA-BSE image, by Figure 6 It can be seen that the main peak of the sample's XRD pattern corresponds perfectly to the standard diffraction peak of the main phase CeFe2, the diffraction peaks are sharp and symmetrical with low baseline noise, and the crystal is well-crystallized; only a small amount of Fe is associated with it. 23 Zr6 is a beneficial auxiliary phase, and no harmful impurity phase diffraction peaks appeared. Figure 7 It can be seen that the sample matrix is ​​dense and flat, with a uniform distribution of primary and secondary phases, and only a small amount of fine precipitates are present, without any continuous coarse and harmful impurities.

[0151] Single-factor experiment (screening of key process parameters):

[0152] To accurately determine the optimal values ​​of key parameters in the intelligent design process and eliminate parameter interaction interference, this experiment adopted a single-factor variable method. Only one process parameter was changed in each experiment, while the remaining parameters remained the same as those in Example 1. The remanence (Br) and coercivity (H) of the materials were tested. cj ), Maximum magnetic energy product ((BH) max The optimal parameter range was selected, and the experimental results and analysis are as follows:

[0153] 1. Single-factor experiment 1: The effect of annealing temperature on the magnetic properties of the material is shown in Table 1.

[0154]

[0155] Results analysis (based on Table 1):

[0156] When the annealing temperature is below the optimal value (900℃): the thermodynamic conditions are insufficient, the element diffusion rate is slow, the element exchange between the alloy added at the grain boundary and the main phase is insufficient, the phase transformation is incomplete, a large number of metastable phases exist, the compositional uniformity at the grain boundary is poor, and the resistance to the movement of magnetic domain walls is weak, so the magnetic properties are low.

[0157] When the annealing temperature is higher than the optimal value (900℃) (see...) Figure 8 Excessively high temperatures lead to abnormal grain growth, reduced grain boundary area, and decreased resistance to magnetic domain wall movement. At the same time, the main phase is prone to decomposition at high temperatures, precipitating coarsened Fe phase, which disrupts the continuity of the main phase, hinders magnetic flux transmission, and thus significantly reduces magnetic properties.

[0158] 2. Single-factor experiment 2: The effect of annealing time on the magnetic properties of the material is shown in Table 2.

[0159]

[0160] Results analysis (based on Table 2):

[0161] When the annealing time is lower than the optimal value (45 days): element diffusion is insufficient, the enrichment or depletion of components at the grain boundaries is not eliminated, the phase structure does not reach thermodynamic equilibrium, the amount of beneficial grain boundary phases generated is insufficient, and the grain boundary bonding force is weak. Therefore, the magnetic properties gradually increase with the extension of the annealing time.

[0162] When the annealing time is higher than the optimal value (45 days) (see...) Figure 9 The phase structure has basically reached equilibrium, and the formation of beneficial grain boundary phases tends to be saturated. Continuing to extend the annealing time will not further improve the phase structure and composition uniformity. At the same time, prolonged high temperature will cause a small number of grains to grow, which will have a slight negative impact on magnetic properties and increase production energy consumption and costs, which is of no practical significance.

[0163] 3. Single-factor experiment 3: The effect of grain boundary addition mass fraction on the magnetic properties of the material is shown in Table 3.

[0164]

[0165] Results analysis (based on Table 3):

[0166] When the mass fraction of grain boundary addition is lower than the optimal value (5%): the added alloy is insufficient to completely cover the surface of the main phase grains, and cannot fully optimize the grain boundary composition and structure. The effect of grain refinement and stabilization of phase structure is limited. The grain boundary has insufficient resistance to the movement of magnetic domain walls, so the magnetic properties are low.

[0167] When the mass fraction of grain boundary addition is higher than the optimal value (5%) (see...) Figure 10 Excessive addition of alloys forms thick grain boundary phases at grain boundaries, which hinders the transmission of magnetic flux and leads to a decrease in remanence. At the same time, the added alloys tend to agglomerate, which disrupts the continuity of the main phase and weakens the magnetic coupling effect. Therefore, the coercivity and maximum magnetic energy product decrease with the increase of the amount added.

[0168] 4. Single-factor experiment 4: The effect of heating rate on the magnetic properties of the material is shown in Table 4.

[0169]

[0170] Results analysis (based on Table 4):

[0171] When the heating rate is lower than the optimal value (10K / min): the long-term low temperature stage causes elements to precipitate prematurely, forming an uneven phase structure, uneven grain distribution, and poor magnetic domain structure integrity; at the same time, the production efficiency is low, energy consumption increases, and therefore the magnetic properties are low.

[0172] When the heating rate is higher than the optimal value (10 K / min) (see...) Figure 11Large temperature differences between the inside and outside of the material generate significant thermal stress, leading to grain boundary cracking, grain distortion, and even thermally induced defects. This disrupts the continuity of the magnetic domain structure, hinders magnetic flux transmission, and thus significantly reduces magnetic properties.

[0173] 5. Single-factor experiment 5: The effect of Ce substitution ratio on the magnetic properties of the material is shown in Table 5.

[0174]

[0175] Results analysis (based on Table 5):

[0176] When the Ce substitution ratio is below the optimal value (5%): the cost reduction effect of Ce is not significant, and Ce2Fe is formed by Ce and Fe. 17 The insufficient formation of beneficial grain boundary phases makes it impossible to fully optimize the grain boundary structure, resulting in limited improvement in magnetic properties and a lack of significant cost advantages.

[0177] When the Ce substitution rate is higher than the optimal value (5%) (see...) Figure 12 Ce has a lower magnetic moment than Nd. Excessive substitution leads to a decrease in the magnetic moment of the main phase and the precipitation of harmful phases such as CeFe3, which disrupts the continuity of the main phase. Although the cost reduction rate is further improved, the magnetic properties are significantly degraded, which cannot meet the requirements of high-end applications. Therefore, 5% is the optimal balance point between performance and cost.

[0178] Testing of material performance indicators:

[0179] 1. Testing Basis and Methods

[0180] To comprehensively evaluate the overall performance of the materials prepared by the process of this invention, the samples of Examples 1-3 were tested for the following indicators in accordance with national standards and industry specifications:

[0181] Magnetic properties (Br, H) cj (BH) max According to GB / T 3217-2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials", the test was conducted using a permanent magnet material comprehensive measuring instrument (model: NIM-2000) at an ambient temperature of 25℃.

[0182] Temperature coefficient (α(B) r ), β(H cj According to GB / T 24270-2009 "Method for Measurement of Temperature Coefficient of Magnetic Properties of Permanent Magnet Materials", the magnetic properties are tested every 20°C within the temperature range of -40°C to 150°C, and the temperature coefficient is calculated.

[0183] Corrosion resistance: According to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test", a neutral salt spray test (NSS) was used for 1000 hours, and the corrosion rate was calculated.

[0184] Mechanical properties (compressive strength): tested using a universal testing machine (model: WDW-100) at a loading rate of 2 mm / min;

[0185] 2. Test Results

[0186] (1) The results of the magnetic properties test are shown in Table 6.

[0187]

[0188] As shown in Table 6, the remanence Br of the samples in Examples 1-3 is 1.41-1.43T, and the coercivity H is... cj The energy product is 15.2-1.54 kOe, and the maximum energy product (BH) is... max The magnetic properties of the sample are 42.5-43.2 MGOe, indicating excellent magnetic properties. In this invention, intelligent composition design is based on a phase diagram database, and harmful phases (such as Fe) are eliminated through a phase region matching algorithm. x Nd 1-x The large-scale precipitation of Nd2Fe ensures the formation of the main phase (Nd2Fe). 14 B, Ce2Fe 14 B) purity and continuity; simultaneously, the performance prediction model optimizes the elemental ratio, making NdxFe 23 Zr 6-x Ce2Fe 17 The uniform distribution of beneficial grain boundary phases refines the grains, increases the grain boundary area, and enhances the resistance to magnetic domain wall movement, thereby significantly improving magnetic properties.

[0189] (2) The temperature coefficient test results are shown in Table 7.

[0190]

[0191] As shown in Table 7, the remanence temperature coefficient α(B) of the samples in Examples 1-3 is... r The coercivity temperature coefficient β(H) is -0.031 to -0.032% / ℃. cj The concentration of Fe is -0.44 to -0.45% at ℃. In this invention, the Fe formed by the reaction of Zr and Fe is... 23 Intermetallic compounds such as Zr6 and Fe2Zr possess high melting points and excellent thermal stability, which can suppress phase transformations and grain growth under temperature changes. Simultaneously, intelligently optimized annealing temperatures and times ensure thermodynamic equilibrium of the phase structure, reducing the presence of metastable phases. These factors contribute to a more stable magnetic domain structure and slower decay of magnetic properties across a wide temperature range.

[0192] (3) The corrosion resistance test results are shown in Table 8.

[0193]

[0194] As shown in Table 7, the salt spray corrosion rates of the samples in Examples 1-3 were 0.0023-0.0025 mm / a, indicating that the samples had excellent corrosion resistance. In this invention, the oxide film formed by the appropriate addition of Ce element can block the corrosive medium (Cl... - The Zr element enhances the chemical stability of grain boundaries and reduces corrosion channels at grain boundaries. The intelligently designed uniform phase distribution and dense grain boundary structure further reduce the penetration rate of corrosive media.

[0195] (4) The mechanical performance test results are shown in Table 9.

[0196]

[0197] As shown in Table 9, the compressive strength of the samples in Examples 1-3 is 1248-1265 MPa, indicating good compressive strength. In this invention, refined grains increase the grain boundary area and enhance grain boundary bonding. According to the Hall-Page relation, grain refinement can significantly improve the mechanical strength of the material; simultaneously, the addition of alloys to the grain boundaries forms intermetallic compounds (such as Fe). 23 Zr6 and CeFe2 are evenly distributed at the grain boundaries, playing a role in dispersion strengthening and enhancing the material's resistance to deformation.

[0198] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A smart design process for grain boundary alloying of dual-phase Nd-Ce-Fe-B rare earth permanent magnet materials, characterized in that, Includes the following steps: (1) Constructing a phase diagram database for multi-component systems: Based on the main phase structure of dual-main-phase Nd-Ce-Fe-B permanent magnet materials, a phase diagram database for Nd-Fe-Zr and Ce-Fe-Zr systems was constructed, selecting rare earth elements Nd and Ce as well as transition metals Fe and Zr. The alloy system was prepared using a balanced process to adjust the composition, and phase characterization analysis was conducted to obtain experimental data on the equilibrium phase under different element ratios. The composition ranges of each element were defined, including Nd, Ce, Fe, and Zr, with the total ratio normalized to 100 at.%, of which Nd content was 3.6-43.1 at.%, Ce content was 0-30.94 at.%, Zr content was 1.6-18.9 at.%, and Fe content was 35.5-94.8 at.%. The system recorded and stored the phase types, elemental composition of each phase, phase region distribution boundaries, and component thresholds for easily precipitating harmful phases corresponding to different compositions. At the same time, beneficial phases and harmful impurity phases in the system were distinguished and marked to form a phase diagram database with phase screening and constraint functions. (2) Intelligent composition design based on intelligent algorithm model: According to the preset lower limit of permanent magnetic performance index as a constraint, the phase region matching algorithm is first called to traverse all the composition ratios in the phase diagram database, eliminate the ratios with harmful impurity phases, and screen to obtain a set of candidate compositions containing only beneficial phases; then, the machine learning performance prediction model is used to establish the correlation between element composition and permanent magnetic performance based on historical experimental data, and the candidate composition set is iteratively optimized to finally output the optimal alloy composition ratio that simultaneously meets the preset permanent magnetic performance requirements and has no harmful impurity phases. (3) Intelligent optimization of process parameters: Based on single-factor experiments and multi-factor coupling analysis, intelligent optimization of process parameters: annealing temperature 850-950℃, annealing time 35-50 days, heating rate 8-12K / min, grain boundary addition mass fraction 4%-6%, and cooling method is furnace cooling or segmented cooling. (4) Material preparation: The dual-phase Nd-Ce-Fe-B powder and the intelligently designed grain boundary alloy powder were mixed evenly in proportion, sintered under argon protection, and then annealed according to the optimized process parameters to obtain the dual-phase Nd-Ce-Fe-B rare earth permanent magnet material.

2. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 1, characterized in that, The data in step (1) includes the identification phase and EPMA component analysis results under different element ratios.

3. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 1, characterized in that, The intelligent algorithm model described in step (2) includes a phase region matching algorithm and a performance prediction model. The phase region matching algorithm is used to screen the element ratio of the phase without harmful impurities. The performance prediction model is based on a machine learning algorithm, with phase composition and element content as input and magnetic properties as output, to achieve accurate optimization of the ratio.

4. The intelligent design process for grain boundary alloying of dual-phase Nd-Ce-Fe-B rare earth permanent magnet materials according to claim 1, characterized in that, The grain boundary alloying identification phase mentioned in step (2) includes Nd. x Fe 23 Zr 6-x Fe 17 Nd 2-x Zr x Ce2Fe 17 CeFe2, Fe 23 At least two of Zr6 and Fe2Zr are present, and the harmful impurity phase is Fe. x Nd 1-x The content is less than 5 at.%.

5. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 1, characterized in that, The specific method of segmented cooling in step (3) is as follows: first, cool with the furnace to 600°C, and then air cool to room temperature at a rate of 5K / min.

6. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 1, characterized in that, The mixing mass ratio of the dual-phase Nd-Ce-Fe-B powder and the grain boundary added alloy powder in step (4) is 93:7-96:

4.

7. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 6, characterized in that, The mixing method uses a planetary ball mill with a ball milling speed of 200-300 r / min and a ball milling time of 2-4 h.

8. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 1, characterized in that, In step (4), the sintering temperature under argon protection is 1050-1150℃, and the sintering time is 2-4h.

9. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 8, characterized in that, The sintering atmosphere is high-purity argon gas with a purity of ≥99.99%.

10. The intelligent design process for grain boundary alloying of dual-main-phase Nd-Ce-Fe-B rare-earth permanent magnet materials according to claim 1, characterized in that, The main phase of the dual-main-phase Nd-Ce-Fe-B permanent magnet material is Nd2Fe. 14 B and Ce2Fe 14 B, the mass ratio of the two is 1:1-3:1.

Citation Information

Patent Citations

  • Multi-element grain boundary reconstruction method for improving corrosion resistance of mixed rare earth permanent magnet material through 1: 2 phase

    CN114864259A

  • GAN-based high-remanence neodymium iron boron component and process optimization method

    CN121964306A